Providers Perspectives on Tdap Vaccination in Pregnancy Patients [8M]. (May 2017) - Vidrine, Samantha; DeCesare, Julie; Roussos-Ross, Dikea; Ashby, Mary; Floyd, Elizabeth; Peterson, Hanna
Abstract : INTRODUCTION: The CDC recommends Tdap vaccination during pregnancy to increase infants' protection against pertussis. The best time to vaccinate is between 27 and 36 weeks gestation in order to maximize the maternal antibody response and transfer to the infant. This project looks at the providers prospective as to why women are not receiving the vaccine. METHODS: An 8 question survey was sent out to all members of the American College of Obstetricians and Gynecologists District XII. The questions were concerning Tdap vaccination in pregnancy. Responses were received from 139 providers. RESULTS: According to the survey, 83.4% of obstetricians universally offer Tdap vaccinations in the third trimester in their office. Of the patients who are offered the vaccine, 51-75% of patients accept the vaccine. Concern for vaccination safety was the most common response for why patients decline, followed by lack of understanding of importance. 55.9% of providers answered that they encounter barriers in trying to offer Tdap in their practice, and identified was lack of point of care availability (70.3%) as the most common barrier. Difference in vaccination rates between insure types were noted and 59% answered that Medicaid patients are less likely to receive Tdap in the third trimester due to lack of reimbursement. CONCLUSION: The most common reasons cited for patients to not receive Tdap vaccination in the third trimester is concern for safety and lack of understanding of importance. More than half of the providers answered that Medicaid patients are less likely to receive the vaccine due to reimbursement and point of care issues.